14C-Warfarin Excretion in the Rat - Losito, R; Rousseau, Marie-Andree (Thrombosis and Haemostasis, 1972)
The excretion of 14C-warfarin and its metabolites in bile and urine was studied in rats with or without biliary fistulas. After oral administration of the drug, 39.4% of the 14C could be isolated in the bile and 18.9% in the urine at the end of 96 h. After i.v. administration 47.5% and 21.3% of the 14C was found in the bile and the urine respectively. In animals without biliary fistulas, 41% of the dose was found in the urine after intravenous injection and 43% via the oral route. In bile, five radioactive components were detected; one component was identified as warfarin and represented 3.9% (oral) and 8.5% (I.V.) of the 14C in the bile. Another component of bile (17.7% to 19.6% of 14C) was identified as 6-hydroxywarfarin. In urine, three 14C components were found; the major component in urine was found to be warfarin and represented close to 75% of the 14C in the urine. Two 14C metabolites which were present in the urine were also present in the bile. Biliary fistula did not prevent radioactivity from being discharged into the urine. In feces, 9.3% of the dose could be isolated and was similar to warfarin. In the liver, at the end of four hours, 19% of the 14C could be isolated; only 74% of this could be extracted and was established as warfarin. The liver failed to show the presence of any metabolites.